Reputation transmission without benefit to the reporter: A behavioral underpinning of markets in experimental focus - Kenju Kamei; Louis Putterman (Brown University, Department of Economics, 2015)
Reputation is a commonly cited check on opportunism in economic and social interactions. But it is often unclear what would motivate an agent to report another's behavior when the pool of potential partners is large and it is easy enough for an aggrieved player to move on. We argue that behavioral or social preference motivations may solve this conundrum. In a laboratory experiment in which subjects lack any private material incentive to report partners' actions, we find that most cooperators incur a cost to report a defecting partner when this has the potential to deprive the latter of future gains and to help his next partner.
Keywords: C91; D03; D63; 330; reputation; prisoners' dilemma; experiment; punishment; communication; costly reporting; social preference; inequity aversion